The COVID-19 pandemic and the gender gap in newly created domains of household labor - Abromaviciute, Jurgita; Carian, Emily K. (Sociological Perspectives, 2022)
In this study, we draw on interview data from 62 matched different-sex, dual-career spouses raising young children to examine the mechanisms behind the gender gap in household labor during the COVID-19 pandemic. We argue that the pandemic represents a unique case of social uncertainty and an opportunity to observe how structural conditions shape the gendered division of household labor. We find that under the rapid social transformation imposed by the pandemic, gender serves as an anchor and orienting frame for couples with young children. We argue that the pandemic (1) expanded traditional gender expectations to new domains of household labor and (2) heightened the importance of gendered explanations for the division of labor that justified intra-couple inequality. Our findings suggest that the particular structural conditions that characterize different times of uncertainty work through slightly different mechanisms, yet produce the same outcome: gender inequality, with long-lasting and wide-ranging implications. © The Author(s) 2022.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; famille; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

COVID-19 and gender inequity in science: Consistent harm over time - Caldarulo, Mattia; Olsen, Jared; Frandell, Ashlee; Islam, Shaika; Johnson, Timothy P; Feeney, Mary K; Michalegko, Lesley; Welch, Eric W (PLoS One, 2022)
Stay-at-home-orders, online learning, and work from home policies are some of the responses governments, universities, and other institutions adopted to slow the spread of COVID-19. However, research shows these measures have increased pre-existing gender disparities in the workplace. The working conditions for women during the pandemic worsened due to increased family care responsibilities and unequal distribution of domestic labor. In the academy, working from home has resulted in reduced research time and increased teaching and family care responsibilities, with a larger proportion of that burden falling to women. We investigate the persistence of gender inequity among academic scientists resulting from university COVID-19 responses over time. We draw on two surveys administered in May 2020 and May 2021 to university-based biologists, biochemists, and civil and environmental engineers, to analyze how the pandemic response has disproportionately impacted women in academia and the endurance of those inequities. Results show significantly greater negative impacts from the pandemic on women’s research activities and work-life balance, compared to men. We conclude by discussing the implications of our results, and the need for the academy to better predict and adjust to the gender disparities its policies create.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; covid-19; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail gratuit; états-unis

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Les effets de la crise sociosanitaire de la COVID-19 sur la charge mentale des femmes : le vécu de travailleuses de la région de Chaudière-Appalaches. Synthèse - Seery, Annabelle; Forest, Danielle; St-Germain, Lise (Trois-Rivières: Centre de recherche sociale appliquée (CRSA), 2022)
Fiche synthèse 1. Objectifs Intentions : Le but de cette recherche est de «documenter l’impact de la crise sociosanitaire sur la charge mentale des travailleuses de la région [de la Chaudière-Appalaches].» (p. 3) 2. Méthode Échantillon/Matériau : L’échantillon est constitué de 22 femmes résidentes de Lévis, âgées entre 26 et 45 ans. La majorité de ces femmes «occupe un emploi à temps plein et a travaillé au moins une partie de la 1re année de pandémie en télétravail.» (p. 4) De plus, la majorité des participantes habitent avec leur partenaire et ont des enfants.» (p. 4) Instruments : Guide d’entretien semi-directif Type de traitement des données : Analyse de contenu 3. Résumé Les résultats montrent que «[l]a fermeture des écoles et des services de garde de même que la diminution du soutien disponible ont entrainé une augmentation de la charge de travail des femmes au sein de leur famille.» (p. 6) Les résultats révèlent également que «[l]es femmes sont demeurées les responsables du travail à réaliser dans la famille, en plus de voir s’ajouter la responsabilité de l’école à la maison ou le casse-tête de la garde des enfants. [De plus], [l]es femmes proches aidantes ont aussi vu leur charge de travail augmentée en répondant aux besoins de leurs proches dépendants.» (p. 6) Aussi, «[l]es femmes qui ont fait du télétravail ont rencontré plusieurs difficultés à cause du contexte particulier dans lequel elles ont dû travailler (notamment avec les enfants à la maison).» (p. 6) Enfin, les résultats mettent en lumière que «[l]es mères, et encore plus celles ayant des enfants de moins de cinq ans, vivent davantage de détresse psychologique que les pères. La détresse psychologique est aussi plus élevée chez les parents moins aisés financièrement.» (p. 6) Mots-clés charge mentale (5) Chaudière-Appalaches (68) conciliation famille-travail (640) COVID-19 (112) division sexuelle du travail (21) mère (1459) télétravail (16) travail domestique (145)
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; charge mentale; conciliation famille-travail; covid-19; division sexuelle du travail; famille; projet charge mentale; périodes historiques; québec; régions géographiques; santé; santé des travailleuses; thématiques; travail; travail domestique

The entrenchment of the ideal worker norm during the COVID-19 pandemic: Evidence from working mothers in the United States - Zanhour, Mona; Sumpter, Dana (Gender, Work and Organization, 2022)
We study shifts in the ideal worker culture as experienced by working mothers across organizations in the United States during the COVID-19 pandemic. Experiences of 53 interviewees who attended to increased responsibilities across both work and family domains revealed an entrenchment of the ideal worker culture across nearly all organizations and professions. This manifested in three levels: as (1) a reinforced ideal worker culture in the workplace through work intensification, increased competitiveness, and surface-level support; (2) the reinforcing of organizations' ideal worker norms at home, with gendered division of space and labor; and (3) experienced internalized ideal worker norms in the expectations working mothers maintained for themselves. These findings offer insight into the lives of working mothers during the COVID-19 pandemic and the challenges which have pushed many mothers to reduce work hours or leave the workforce. Highlighting the intricate nature of the entrenchment of the ideal worker culture informs implications for theory of gendered organizations and for organizational practice. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; culpabilité des mères; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail des mères; états-unis